2022
DOI: 10.52131/pjhss.2022.1004.0319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance on Islamic Banks Performance: An Evidence from Islamic Banking Industry of Pakistan

Abstract: The objective of our study is to explore the relationship between corporate governance and the performance management of Islamic banks in Pakistan. To fulfill our aim, we used the data of the five central Islamic banks working in Pakistan from 2016–2020. The data was collected from reputable banks' annual reports, and the annual accounts are downloaded from the website of the PSX data portal. For the analysis of the relationship between the variables, we used the OLS methods of research that are useful for pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…This result goes on the line of the result of Ramola and Rangnekar, (2021) [21] that concluded that organization having effective performance management system leads to succession planning process. Also Ali, Mehmood, Ejaz, and Ashraf (2014) [22] argued that performance management can be enhanced by succession management practices such as training and development.…”
Section: Standardized Estimatesmentioning
confidence: 99%
“…This result goes on the line of the result of Ramola and Rangnekar, (2021) [21] that concluded that organization having effective performance management system leads to succession planning process. Also Ali, Mehmood, Ejaz, and Ashraf (2014) [22] argued that performance management can be enhanced by succession management practices such as training and development.…”
Section: Standardized Estimatesmentioning
confidence: 99%
“…SBP issues all the strategies, policies, and credit structure guidelines to the financial sector to ensure the sustainability of financial services. It follows the Basel Accords guidelines/rules and strictly imposes checks and balances on all the commercial banks' activities regarding credit risk management (CRM), non-performing loans (NPLs), loan procedure, and credit strategies, which contributes significantly to the growth of the banking sector (Khan, 2023).…”
Section: State Bank Of Pakistanmentioning
confidence: 99%
“…The banking sector is the backbone of any developing country. Pakistan's banking infrastructure plays a crucial and supportive role in fostering the economic growth and sustainability of the financial sector (Shafiq et al, 2023). According to 'The Pakistan Financial Institutions Ordinance 1962,' banks are tasked with collecting and depositing money, making investments, providing services, and being repayable.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, most private universities in Vietnam should have the understanding and drive for satisfaction and retention. On the other hand, students' satisfaction and learning success are critical in developing excellent employees and managers, providing substantial benefits to the growth of a nation's economy and society [19][20][21] . In the context of a competitive educational market, student retention is seen as a critical statistic for determining how well an educational institution satisfies the demands of its students 22 .…”
Section: Introductionmentioning
confidence: 99%